Anais do I Simpósio Brasileiro de Investigação de Doenças Neuromusculares - Fávero, Francis Meire; Oliveira, Acary Souza Bulle; Voos, Mariana Callil; Sá, Cristina dos Santos Cardoso de; Caromano, Fátima Aparecida (Revista Neurociências, 2015)
.